Fundamental solution of steady oscillations for porous materials with dual-phase-lag model in micropolar thermoelasticity. Issue 4 (4th July 2019) - Biswas, Siddhartha
Abstract: This article deals with the study of propagation of plane waves in an isotropic thermoelastic medium for porous materials with the linear theory of micropolar thermoelasticity. The problem is treated in the context of dual-phase-lag model of thermoelasticity. It is found that, for one-dimensional model, there exists three longitudinal waves, namely elastic (E-mode), thermal (T-mode), and volume fraction (V-mode) in addition to transverse waves which get decoupled from rest of the motion and not affected by thermal and volume fraction fields. In case of steady oscillations, the fundamental solution of the system of differential equations in terms of elementary functions has been constructed. The phase velocity and attenuation coefficient of these waves are computed numerically and presented graphically.